PAI Teacher's Efforts in The Formation of Student Character in MIN 13 Pidie Jaya - Nurulaini (Kamara Journal, 2025)
This study focuses on the importance of character development in students from an early age as a foundation for building a strong personality, as well as the role of Islamic Religious Education Teachers (GPAI) in integrating Islamic values into students' daily lives. The study aims to understand the fundamental concept of character development, the efforts of GPAI in shaping students' character at MIN 13 Pidie Jaya, and the supporting and inhibiting factors in the process. Using a qualitative approach, data were collected through observation, interviews, and documentation. The research findings indicate that character development in the madrasa emphasizes key values such as honesty, responsibility, patience, and empathy. The efforts of GPAI are carried out through methods such as role modeling, spiritual reminders (tadzkirah), guidance, and regular activities like congregational prayers and Islamic camp programs (pesantren kilat). Supporting factors include a conducive school environment and family involvement, while challenges include the lack of consistency in value application at home and external social influences. The study recommends ongoing collaboration between the madrasa, families, and the community to ensure the effective and sustainable implementation of character education.